Analisis Komposisi Hasil Tangkapan Ikan dengan Alat Tangkap Purse Seine di Pelabuhan Perikanan Samudera (PPS) Nizam Zachman Jakarta - Dina Dewi Fitriana; Achmad Kusyairi; Alif Astagia (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Indonesia as the largest archipelagic country has significant fisheries potential, one of which is through the Nizam Zachman Ocean Fishing Port (PPS) in Jakarta. This port is a central hub for fish landing and distribution in the DKI Jakarta area and its surroundings, particularly with the use of purse seine fishing gear. This study aims to analyze the composition of fish catches using purse seine at the Nizam Zachman Ocean Fishing Port and identify the species caught. The research method includes direct observation of the catch, documentation, and weighing of each fish species. Primary data is obtained from field observations, while secondary data is gathered from relevant literature. Composition analysis is carried out by calculating the percentage of each fish species relative to the total catch, using the formula Kj = (Ni/N) x 100%. During the study, with a sample of 67 vessels, 31 fish species were recorded, with dominant species including skipjack tuna (Katsuwonus pelamis) at 55.42%, scads (Decapterus spp.) at 14.11%, bigeye tuna (Thunnus obesus) at 13.55%, and yellowfin tuna (Thunnus albacares) at 10.33%. The variation in catches was influenced by fishing season, fishing location, vessel size and operational duration, fishing technology and equipment, and weather conditions.